A Pragmatic Study of Speech Acts in the Twitter Posts of Four Prominent Music Judges - Sianipar, Maria Olivia Christina; Sumarsih; Husein, Rahmad (Forum for Linguistic Studies, 2025)
This study investigates the use of speech acts in social media status updates by four renowned music judges—Simon Cowell, Howie Mandel, Luke Bryan, and Lionel Richie through the lens of Searle’s speech act theory. Status updates, a key feature of social media platforms such as Twitter, serve as tools for self-expression, interaction, and the dissemination of information, including events, promotions, and personal reflections. Adopting a descriptive qualitative design, this research analyzes words, phrases, sentences, expressions, and moods contained in the Twitter posts of the selected public figures, with the primary aim of identifying the types and realizations of speech acts employed. Findings reveal that representative acts constitute a dominant category across the four judges, functioning mainly as reports. Directive acts are also frequently employed, particularly in the form of invitations. Expressive acts are common, with Lionel Richie showing the highest usage, though Howie Mandel, Luke Bryan, and Simon Cowell also rely heavily on them, often in the form of compliments. Commissive acts appear less frequently; Luke Bryan and Simon Cowell each employed one instance, while Lionel Richie used two, typically as promises. Declarative acts, the rarest type, were identified in posts by Richie, Bryan, and Cowell, with Cowell using them most frequently to announce awards and graduations. Notably, Howie Mandel did not employ commissive or declarative acts. Overall, the findings highlight both similarities and distinctions in the communicative styles of these judges. All four demonstrate active engagement through expressive and directive acts, underscoring the role of speech acts in shaping their online presence and interaction with audiences.